A Review of Biofuels Research in Nigeria - Odetoye, T. E.; Ajala, E. O.; Ogunniyi, D. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Biofuels are attracting a lot of research attention as a source of renewable energy due to environmental benefits and prospects of energy security. The expectation of the global community is particularly high towards Sub-Saharan African countries like Nigeria to meet the growing bioenergy needs by harnessing the abundant supply of biomass feedstock. However, lack of home-grown technology has been one of the major drawbacks of biofuel industrialization in Nigeria. Although a reasonable amount of biofuel research effort has been embarked on locally in Nigeria, most of these research works have remained on the shelf instead of being translated into commercial production. This paper reviews some biofuel research work done on Nigerian biomass. It recommends that funding the existing and new biofuel research work in Nigeria and channeling research towards industrialization as important drivers towards biofuel production in Nigeria.